Effectiveness of text messages, calls and e-mail on adherence to medical appointments. Review of systematic reviews and meta-analysis - Palacios Barahona, Arlex Uriel; Hernández Rendón, Maritza; Gaviria Lopez, Andrés; Guerra Herrera, Ana Cristina; Valencia Diaz, Edison; Martinez Herrera, Eliana (CES Medicina, 2018)
Background: Mobile phones and all other forms of modern communication such as the Internet and instant messaging applications have become tools to improve attendance rates for medical appointments. Objectives: To evaluate the effectiveness of reminders to improve adherence to medical appointments. Methods: An overview of studies comparing the effectiveness and attendance rates for medical appointments between patients that did and did not receive reminders. Also, a meta-analysis was conducted to estimate the overall effect of keeping appointments depending on the age of the patients. Results: Seven reviews were identified which show that Short Message Service (SMS) improves adherence to medical appointments. However, the meta-analysis showed a relative risk of 1,09 (CI 95%: 1,03 -1,11) for people with ages between 24 – 40 and 1,09 (CI 95% 1,05 – 1,14) for people with ages between 50 – 63, with regard to appointment assistance via SMS. Conclusions: The use of SMS reminders has a positive impact on medical appointment attendance. However, while reviewing the impact by age groups no differences were found.